2012
DOI: 10.1177/2041386612441735
|View full text |Cite
|
Sign up to set email alerts
|

From bad to worse

Abstract: Poor employee–customer interactions influence customer satisfaction and employee well-being. In studying these negative exchanges, researchers tend to take either the perspective of the customer (i.e., the problem is service failure) or the employee (i.e., the problem is the difficult customer). We review these two literatures to show that the inputs, processes, and outcomes of these two perspectives are linked in a way that creates a negative exchange spiral. We argue that this is an “open-loop” spiral becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(43 citation statements)
references
References 152 publications
(203 reference statements)
0
42
0
1
Order By: Relevance
“…To cope with feelings stemming from negative workplace events, employees may turn to dysfunctional coping strategies and counterproductive workplace behaviors. In doing so, the original victim of customer mistreatment may breed a cycle of negativity that results in further problems for coworkers and for the organization (Groth & Grandey, 2012). Our research, however, suggests that turning to more functional behaviors can assist employees in coping with the negative emotions arising from mistreatment by promoting the experience of positive emotions.…”
Section: Practical Implicationsmentioning
confidence: 81%
See 2 more Smart Citations
“…To cope with feelings stemming from negative workplace events, employees may turn to dysfunctional coping strategies and counterproductive workplace behaviors. In doing so, the original victim of customer mistreatment may breed a cycle of negativity that results in further problems for coworkers and for the organization (Groth & Grandey, 2012). Our research, however, suggests that turning to more functional behaviors can assist employees in coping with the negative emotions arising from mistreatment by promoting the experience of positive emotions.…”
Section: Practical Implicationsmentioning
confidence: 81%
“…In service contexts, direct retaliation against the mistreating customer may not be possible due to the briefness of most service encounters. Service employees may therefore displace their retaliation toward agents that are perceived to be similar to the initial perpetrator (i.e., other customers, Groth & Grandey, 2012). This is supported by Sjöström and Gollwitzer (2015) who found that victims report higher levels of satisfaction and lower levels of regret when they are provided an opportunity to displace their revenge against an alternative target that belonged to the same group as the initial perpetrator.…”
Section: Study 2: Helping Toward Other Customers and Customer Orientamentioning
confidence: 93%
See 1 more Smart Citation
“…In the literature, supervisors and colleagues are examined as possible sources both of support and of aggression. In service-sector organizations, conversely, users have rarely been considered as possible sources of support: the focus has been almost exclusively on the negative side of the relationship with “others.” Thus, disproportionate requests (Dormann and Zapf, 2004; Dudenhöffer and Dormann, 2013, 2015), customer mistreatment (Koopmann et al, 2015), or aggressive behaviors (LeBlanc and Kelloway, 2002; Viotti et al, 2015) have been considered to be factors that decrease job satisfaction and psychological well-being, contribute to developing stress, burnout, and the spiraling of negative exchanges between employees and customers (Groth and Grandey, 2012), and directly or indirectly enhance an employee’s intention to leave an organization (Lee and Ashforth, 1996; Jourdain and Chênevert, 2010). However, when service workers are asked why they have chosen their jobs (Maslach, 1982), they often declare their interest in “dealing with people” (Zimmermann et al, 2011, p. 31), thus implying that the motivational processes among service workers is often based on their interest in building a positive relationship with customers (users, patients, students, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, changing one dimension could affect the others in a dynamic and longitudinal way (Bringmann, Ferrer, Hamaker, Borsboom, & Tuerlinckx, 2018;Bringmann, Lemmens, Huibers, Borsboom, & Tuerlinckx, 2015;Hamaker, Asparouhov, Brose, Schmiedek, & Muthén, 2018). Such spillovers may be either positive (Hanson, Hammer, & Colton, 2006;Sirgy et al, 2001) or negative (Groth & Grandey, 2012;Stoetzer, Ahlberg, Bergman, Hallsten, & Lundberg, 2010).…”
mentioning
confidence: 99%